Image transfer from malls to stores and its influence on shopping values and mall patronage: The role of self-congruity. (November 2017) - El Hedhli, Kamel; Zourrig, Haithem; Park, Jeongsoo
Abstract: Little research attention has been paid to the image transference from a shopping mall to its stores. The study reported in this article proposes an integrative model dealing with the image transference phenomenon from malls to stores and its implications in terms of creating value for shoppers and enticing mall patronage. Structural equation modeling is applied to data collected from shoppers in two urban North-Amercian shopping malls. The findings are broadly supportive of the proposed model. Mall image spills over the image of the stores located in the mall, and this occurs through a shopper's self-congruity mechanism. Furthermore, the mall's image dimensions influence hedonic shopping value through self-congruity. The stores' image dimensions differentially influence utilitarian and hedonic shopping values assessments. Both types of shopping values are strong drivers of mall patronage. The study also discusses the implications of the findings as well as its limitations and directions for future research.